Oxide entrainment structures in horizontal running systems - Jolly, Mark R.; Reilly, C.; Green, N. R. (Minerals, Metals & Materials Society, 2009)
During the transient phase of filling a casting running system surface turbulence can cause the entrainment of oxide films into the bulk liquid. Research has shown that these are detrimental to the material’s integrity. Common mechanisms for this entrainment include returning waves, arising during filling of the runner bar, and plunging jets, found when pouring into a basin. One of these, the returning wave, has been studied in greater depth, using real-time X-ray and process modelling techniques alongside the application of physical principals. It has been concluded that when developed, returning waves cannot attain the more stable and less entraining tranquil flow regime desirable in the running system of castings.
Keywords: Casting; Oxide; Quality Assessment; Entrainment; Running System